2019
DOI: 10.1001/jamafacial.2018.1716
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Ecchymosis and Edema After Creation of Subperiosteal Tunnels in Rhinoplasty

Abstract: and edema are commonly associated with rhinoplasty and are the principal limiting factors for return to daily activities after rhinoplasty. Several methods have been evaluated to minimize these sequelae including creation of subperiosteal tunnels, which involves elevating the vascular periosteal layer, preserving it from trauma when creating osteotomies.OBJECTIVE To assess the efficacy of the creation of subperiosteal tunnels prior to lateral osteotomies during rhinoplasty for reducing postoperative ecchymosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 7 publications
0
17
4
Order By: Relevance
“…In a recent meta-analysis, Kim et al 19 have concluded that there was no significant difference in postoperative eyelid ecchymosis and edema whether osteotomy was done internally or externally. Many studies discussed the effect of periosteal tunneling on periorbital sequelae before osteotomy with conflicting results 20–23 . On the contrary, the effect of complete subperiosteal dissection before osteotomy (like we did in our present study) has not been measured objectively in the literature.…”
Section: Discussioncontrasting
confidence: 52%
“…In a recent meta-analysis, Kim et al 19 have concluded that there was no significant difference in postoperative eyelid ecchymosis and edema whether osteotomy was done internally or externally. Many studies discussed the effect of periosteal tunneling on periorbital sequelae before osteotomy with conflicting results 20–23 . On the contrary, the effect of complete subperiosteal dissection before osteotomy (like we did in our present study) has not been measured objectively in the literature.…”
Section: Discussioncontrasting
confidence: 52%
“…Osteotomy is performed with the goals of straightening a deviated dorsum, narrowing the nasal dorsum, and opening the nasal vault [ 11 ]. Eyelid edema and ecchymosis, which are the most common postoperative complications of osteotomy, can be caused by damage to arteries or veins and soft tissue injuries during lateral osteotomy [ 5 ]. In lateral osteotomy, considerable force is delivered to the soft tissues and bones to mobilize the nasal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral osteotomy can be performed after periosteal elevation. A subperiosteal tunnel is formed by elevating the periosteum and upper layer from the bony cortex in the path of the osteotomy [ 5 ]. The goal of subperiosteal tunneling is to protect the blood vessels and to reduce periosteal injury during osteotomy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the six articles reviewed, one concluded that there were no significant differences in the measured parameters between the two methods, indicating that no single method was superior to the other [2]. Another of the articles that was analyzed, by El-Sisi et al [3], dealt with external perforating osteotomy, in which the tunneling method is totally different from that used in internal osteotomy.…”
mentioning
confidence: 99%